An Investigation Into Information Design Of Nutritional Labels In Malaysia - Koh, Pouline Chai Lin (2017)
This research investigates information design of nutritional labels in Malaysia. In particular, three areas are further examined including: 1) the elements and design features applied in the nutritional labels; 2) the use of nutritional labels among Malaysian consumers; and 3) the governance parties including key stakeholders such as regulators, producers, creators, design practitioners and researchers related to nutritional labels in Malaysia. Objectively, this study employs a mixed method including evaluating the existing nutritional labels design in Malaysia through content analysis, surveying the use of nutritional labels among consumers, and the views of key stakeholders are gathered in interviews.